Study of Digital Marketing Strategy: Case Study of SMEs in Cocoa Product Industry in West Sulawesi Province - Adha, Wahyu Maulid; Mas’ud, Anis Anshari; Erwin, Erwin (AIBPM Publisher, 2023)
The purpose of this research is to examine digital marketing strategies for processed cocoa products, a leading commodity in West Sulawesi Province, Indonesia. The goal is to facilitate access to the global market through the application of digital marketing strategies, offering solutions for cocoa product entrepreneurs in West Sulawesi Province to reach a wider audience. The study was conducted in West Sulawesi Province, Indonesia, with 94 respondents from cocoa-processed product SMEs actively utilizing digital media as a marketing tool. Quantitative methods were employed, and data were collected through a survey questionnaire, which was then analyzed using structural equation modeling (SEM). The respondents were affiliated with businesses fostered by the West Sulawesi Cooperatives and SMEs Office. The results indicated that the adoption of e-commerce by Cocoa Product SMEs is an alternative solution for implementing sustainable digital marketing strategies. The findings from this study can serve as valuable input for SMEs producing processed cocoa products, enabling them to maximize the use of e-commerce to enter the global market.